Working From Home Policy for Indonesia’s State Civil Apparatus: General Propositions - Prasetyo, Antonius Galih; Sari, Maria Dika Puspita (KnE Social Sciences, 2022)
The COVID-19 pandemic has accelerated the pace of change within the public sector. In Indonesia, one of the most conspicuous transformations can be seen in the introduction of working from home (WFH) practices among public sector employees who are part of the State Civil Apparatus. Before the pandemic, WFH had been proposed as an alternative style of work for the public sector with stipulated requirements as a cue to join the global trend of implementing WFH for employees in the public sector. However, it was only through the pandemic that the vast realization of WFH was done thanks to the health risk factor and the availability of technology. In the absence of comprehensive and official formal evaluation, this paper made use of the findings from previous studies as the basis of evaluating the WFH policy among the State Civil Apparatus. A literature review was conducted and some general propositions regarding WFH policies in the future were developed. Keywords: working from home, State Civil Apparatus, COVID-19 pandemic, policy, evaluation